Dukungan Sosial Pasien Yang Terkonfirmasi Covid-19 - Nonok Karlina; Arie Ardiyanti Rufaedah; Rosalia Rahayu (JURNAL KESEHATAN MERCUSUAR, 2022)
The impact of Covid -19 on individuals who are exposed or confirmed to Covid -19 can be a stressor for patients so they need social support in order to overcome stressors that have an impact on the patient's psychology. This study aims to gain an in-depth understanding of the social support of patients with confirmed Covid-19 cases. This type of qualitative research was conducted using a phenomenological approach, and participants were selected through purposive sampling. In total, 7 participants were aged 21 - 45 years. Data were collected through in-depth interviews with open-ended questions. The data were analyzed thematically. The results showed that the social support received by patients who were confirmed to be Covid-19 varied. Social support is very important to provide self-confidence, improve coping mechanisms and quality of life. Social support is very important for patients with Covid-19. Therefore, it is recommended for nurses to do proper planning so that the patient's social support needs can be met.